A comparative study of catheter size effect after direct vision internal urethrotomy for small urethral strictures - Ajmera, Rohit; Saini, Piyush Kumar; Sharma, Keshav; Pawar, Rakesh Ramesh; Yadav, Rohit (International Journal of Research in Medical Sciences, 2024)
Background: Urethral stricture disease is the most common cause of obstructive voiding symptoms in younger males and has always been a challenge for urologists. Optical urethrotomy (OU) has been considered as the standard therapy for anterior urethral and short segments strictures. Methods: In our study 164 consecutive treatment naive and recurrent urethral stricture patients who underwent direct vision internal urethrotomy (DVIU) were retrospectively analyzed. 22Fr urethral catheters were placed for longer durations and small calibre catheters (14 or 16Fr) were preferred for shorter dwell times after DVIU. Catheter dwell times were grouped as <7 and ≥7 days. Results: A total of 164 patients with a mean age of 54.51±11.8 (range: 17 to 85) years were enrolled in the study during the follow-up, 24 (14.6%) patients experienced recurrences during 6 month follow up. The mean postoperative duration of catheterization was 8.47±2.03 and 6.49±1.14 days, in 6 patients with 14/16 Fr and 18 patients with 20 Fr catheter respectively have recurrence with p=0.00802.5 patients with less than 7 days and 19 patients with >7 days had recurrence with p=0.0019. Conclusions: Urethral stricture disease is disease of high recurrence. Factors responsible for recurrence of disease after treatment like-etiology, length of stricture, duration /size of catheter, open or endoscopic procedure. putting a small diameter catheter and short duration of catheterization help in reducing recurrence.